Characterization of New Monoclonal PF4-Specific Antibodies as Useful Tools for Studies on Typical and Autoimmune Heparin-Induced Thrombocytopenia - Vayne, Caroline; Nguyen, Thi-Huong; Rollin, Jérôme; Charuel, Noémie; Poupon, Anne; Pouplard, Claire; Normann, Nicole; Gruel, Yves; Greinacher, Andreas (Thrombosis and Haemostasis, 2020)
Background Heparin-induced thrombocytopenia (HIT) is typically caused by platelet-activating immunoglobulin G (IgG) antibodies (Abs) against platelet factor 4 (PF4) complexed with heparin (H). Much less frequent “autoimmune” HIT is distinguished from typical HIT by platelet activation without heparin and the presence of both anti-PF4/H and anti-PF4 IgG. We developed three murine monoclonal anti-PF4 Abs with a human Fc-part, 1E12, 1C12, and 2E1, resembling autoimmune HIT Abs.Objectives To characterize 1E12, 1C12, and 2E1 in comparison to the heparin-dependent monoclonal anti-PF4/H Abs 5B9 and KKO, and polyclonal Abs from patients with typical HIT (group-2) and autoimmune HIT (group-3).Methods Interactions of Abs with PF4 and PF4/H were studied by enzyme-linked-immunosorbent assay, single-molecule force spectroscopy, isothermal titration calorimetry, and dynamic light scattering. Serotonin release assay and heparin-induced platelet activation assay were used to assess platelet activation. The binding sites of monoclonal Abs on PF4 were predicted in silico (MAbTope method).Results 1C12, 1E12, and 2E1 displayed higher affinity for PF4/H complexes than 5B9 and KKO, comparable to human group-3 Abs. Only 1C12, 1E12, 2E1, and group-3 Abs formed large complexes with native PF4, and activated platelets without heparin. The predicted binding sites of 1C12, 1E12, and 2E1 on PF4 differed from those of KKO and 5B9, but were close to each other. 2E1 exhibited unique bivalent binding, involving its antigen recognition site to PF4 and charge-dependent interactions with heparin.Conclusion 1C12, 1E12, and 2E1 are tools for studying the pathophysiology of autoimmune HIT. 2E1 provides evidence for a new binding mechanism of HIT Abs.
Keywords: platelet factor 4; monoclonal antibodies; heparin; thrombocytopenia